EXPERIÊNCIA URBANA E ROMANCE BRASILEIRO - Gil, Fernando Cerisara (Revista Letras, 2004)
Este trabalho analisa a especificidade da experiência urbana moderna no romance brasileiro, localizando a sua entrada em cena na forma ficcional nos anos de 1930. Urban experience and Brazilian novel Abstract This work analyzes the specificity of the modern urban experience in the Brazilian novel, locating its entrance scene in the fictional form in the years of 1930.